PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) TERHADAP PEMAHAMAN KONSEP IPAS SISWA KELAS IV SD - Rani Permatasari; Maharani Oktavia; Puji Ayurachmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Team Assisted Individualization (TAI) Type on the Understanding of Science Concepts of Grade IV Elementary School Students. This research is an experimental research with a true experimental research type. The population of the study was all students of Elementary School 226 Palembang totaling 138 students. The sample taken was class IV.1 totaling 35 students as an experimental class using the Team Assisted Individualization (TAI) type cooperative learning model and class IV.3 totaling 35 students as a control class using conventional learning. This sampling used a purposive sampling technique. The data collection technique used was a test to measure students' understanding of concepts. The data analysis technique used was the Independent Sample T-test (t-test). The results of this study indicate that there is a significant influence of the Team Assisted Individualization (TAI) type cooperative learning model on the understanding of Science Concepts of grade IV elementary school students.